2013
DOI: 10.1007/s40140-013-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Adenosine in Cerebral Aneurysm Clipping: A Review

Abstract: Management of intracranial aneurysms continues to evolve, with coiling of aneurysms becoming an increasingly used modality. However, for aneurysms which are considered to be ''complex'' due to their size, position, or morphology, clipping continues to be the preferred treatment option. Several techniques can be utilized intraoperatively to facilitate aneurysm exposure and clip ligation. These include deep hypothermic circulatory arrest, endovascular balloon occlusion with suction, and, most commonly, temporary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 30 publications
0
13
0
10
Order By: Relevance
“…The use of adenosine should be avoided in patients with severe reactive airway disease, severe coronary artery stenosis, and preexisting cardiac conduction abnormalities. 183 In addition, one should be cautious with the use of adenosine in patients who are on dipyridamole, carbamazepine, digoxin, and verapamil. These medications are likely to prolong the duration of action of adenosine.…”
Section: Anesthetic Management Of Surgical Clippingmentioning
confidence: 99%
“…The use of adenosine should be avoided in patients with severe reactive airway disease, severe coronary artery stenosis, and preexisting cardiac conduction abnormalities. 183 In addition, one should be cautious with the use of adenosine in patients who are on dipyridamole, carbamazepine, digoxin, and verapamil. These medications are likely to prolong the duration of action of adenosine.…”
Section: Anesthetic Management Of Surgical Clippingmentioning
confidence: 99%
“…Popularized in 2005, this technique effectively induces transient hypotension and facilitates dissection and clip ligation of intracranial aneurysms. 5 This method, however, has risks that limit its use. There are general guidelines for dosing in adults, but the doses can vary, resulting in unpredictable dose responses in patients.…”
Section: Discussionmentioning
confidence: 99%
“…5 There are risks associated with RVP, chief among them are arrhythmias, including ventricular tachycardia and fibrillation. 10,13,16 These are treated by override pacing or, in our case, defibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Chronic smokers without the presence of severe reactive airway disease do not pose any risk of bronchospasm with adenosine. 33 Another situation in which one needs to be cautious with adenosine use was pointed out by a study by Makaryus et al, 16 which reported development of a persistent AV block in patients with pre-existing right bundle branch block, when large doses of adenosine (47 mg over 5 minutes) were used and required postoperative permanent pacemaker implantation. Adenosine action on the coronary vasculature causes vasodilation, and this results in coronary vascular steal phenomenon in patients with cardiac ischemia.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%